TEKNOLOGI VACUM FRYING UNTUK PENGGORENGAN KERIPIK JAMUR TIRAM di DESA TALANG BUBUK PLAJU PALEMBANG - Selastia Yuliati; Tri Widagdo (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
The purpose of this activity is to help partners in order to increase the productivity of the oyster mushroom business group through the application of appropriate technology and skills training for diversification of oyster mushroom products. The implementation method consists of two activities, namely (1) making a vacuum frying machine, and (2) training on mushroom chips processing skills. Making vacuum frying includes the process of planning, manufacturing, testing, and training in the use of machines for work partners. Meanwhile, training for partners includes: (1) providing theories and demonstrations on how to use vacuum frying, (2) training on mushroom chips skills and (3) product marketing training. The results of this science and technology program are the realization of a vacuum frying machine with mushroom capacity specifications of 3.5 kg / process, LPG fueled with automatic temperature control, cooling water circulation, 15 liter cooking oil volume, 900 watt power requirements, dimensions 160 x 100 x 100 cm, with an oil heating temperature of 80 oC and temperature changes between 80 - 90⁰ C, frying time ± 1.5 hours (for one frying time). Mushroom diversification resulted from the training of oyster mushroom processing skills in the form of mushroom chips.